Leaf and tuber resistance to Phytophthora infestans and relationship between these traits in wild potato species - N. M. Zoteyeva; E. A. Porokhovinova; D. A. Fateev; N. A. Chalaya (Труды по прикладной ботанике, генетике и селекции)
Background. Phytophthora infestans (Mont.) de Bary is a well-known serious pathogen that affects a wide range of currently grown potato cultivars. Control of the disease, including the breeding process, is complicated by the fact that leaf resistance to P. infestans is often unrelated to tuber resistance, resulting in the need to identify individual plants with leaf and/or tuber resistance to be used in breeding programs. In view of this, research efforts to identify such sources are quite relevant. The objective was to assess the occurrence of plants with resistance in both organs among different wild species and analyze the relationship between leaf and tuber resistance within them.Material and methods. Assessment of leaf and tuber resistance in 97 accessions belonging to 36 species was carried out under artificial inoculation. Using the data obtained on each individual plant, the connection between leaf and tuber resistance was analyzed by means of the Wilcoxon matched-pairs test and Spearman’s rank-order correlations.Results. The species with more frequent occurrence of plants combining leaf and tuber resistance and the species with the predominance of leaf or tuber resistance were identified. The statistical analysis did not show complete (100%) correlations between leaf and tuber resistance in any of studied species. In some cases, a significant positive or negative correlation between these characters was found. The assessment results for the studied species/accessions can facilitate the search for leaf and/or tuber resistance sources capable of improving potato cultivars susceptible to late blight.